The Effectiveness of Teaching Science By Using A Model Based on Constructive Learning in Developing Critical Thinking Skills and Achievement of Second Intermediate Students in Bishah, Saudi Arabia - Al- Awaid, Asma Hussein Muhammad (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the effectiveness of teaching science by using a Model-based on constructive learning in developing critical thinking skills and achievement of second grade intermediate. The sample of the study consisted of (40) students randomly distributed into two groups: experimental group and the number of its members (20) students studied the third unit of the book of science for the first semester, entitled: (human body organs), using a teaching model based on structural education and the group The officer and the number of members (20) students studied using the usual method of teaching, to achieve the objectives of the study, the lessons of the unit were taught using a constructive learning model. The researcher prepared a critical thinking scale and an achievement test. The two study tools were applied before and after the study groups. Skills of critical thinking and raising the level of educational attainment of second-grade students in science. The study concluded with a set of recommendations, the most important of which are: Developing the programs of preparing teachers of scientific materials and pre-service science, and trying to add courses of teaching methods in the plan of students of the College of Education and the curriculum and methods of teaching science in Saudi universities and holding practical workshops for science teachers at the level of education administration in Bisha governorate. On how to apply the principles of constructive learning in classroom situations.
Keywords: Effectiveness; Constructive Learning; Critical Thinking Skills; Achievement; Second Grade Intermediate Students